An East Asian renaissance : ideas for economic growth - Gill, Indermit Singh, 1961-; Kharas, Homi J., 1954- (World Bank, 2007)
"This book explores the future of East Asia's middle-income countries. Without the advantages of low wages or high skills, and with limited natural resources, East Asian economies are following a new path of regional integration, led by China. Along this path, policy makers must manage a migration of 2 million per month to East Asian cities; a sharp and unprecedented increase in income inequality; and growing discontent with corruption. This new agenda of domestic integration is the main challenge facing East Asia."--Jacket